Emotional Maturity and First Childbirth Anxiety Levels Aged 17-21 Years in Candi Sidoarjo District - Effy Wardati Maryam; Yeni Yeni (Universitas Muhammadiyah Sidoarjo, 2011)
The background of this research by the researcher’s curiosity about the level of emotional maturity and anxiety experienced by mothers who gave birth for the first time at age 17-21 years. The purpose of this study is to determine whether there is a significant correlation between the level of emotional maturity level of anxiety at first birth mothers 17-21 years of age and indicators of what the most dominant influence of emotional maturity and high levels of anxiety. Based on the analysis of obtained results of product moment correlation coefficient rxy ‘correlation with p = -0.167(0.257) > 0.05. this means that relations between the two variables are not significant. Supported also by results of interviews with the related subject of research and data in the field, says that not only emotional maturity factors that influence the level of anxiety a person in the first childbirth, but also the factor of family support, especially husbands and mothers, information about pregnancy and labor that they could get from print and electronic media and the internet which can be accessed with ease, some from their participation in the exercise group became pregnant, briefing the local health clinic doctor or midwife about childbirth and the high level of religiosity. All this is another factor which also makes the low level of anxiety to face the first delivery in mothers 17-21 years of age.